Legal Protection for Doctors in Legal Disputes in Hospitals from the Perspective of Employment Agreements - Wijaya, Deni; Kholib, Abdul; Prasetyo, Handoyo (Pusat Publikasi Nusantara, 2024)
The aim of this study is to find out how the hospital's efforts to protect doctors who work under employment agreements such as permanent doctors and non-permanent doctors at the hospital and find out what the content of the contract agreement for permanent and non permanent doctors working at the Hospital. This research was carried out in two stages: literature research which aims to obtain secondary data as the main source of data including key legal documents, namely Law Number 17 of 2023 concerning Health. The researcher draws the conclusion that the protection in the hospital does not guarantee the certainty of legal protection for doctors. It is very important to create an optimal collective bargaining agreement between the doctor and the hospital so that a Light and Wise Legal Dispute Resolution is created. The research can provide new knowledge related to the construction of employment agreements for doctors working in hospitals.